The Progression of Taiwanese Women's Roles in Officiating Volleyball. Issue 12 (13th August 2017) - Lee, Ping-Chao; Ko, Ling-Mei; Chiu, Yu-Chen
Abstract: As times have changed, women have attempted through various strategies to redefine their rights to attempt to break down gender stereotypes; this finding is particularly evident in women's participation in politics and sport. The aim of this study is to investigate the issues that have hindered and those that have aided the advancement of women's participation in the field of refereeing volleyball in Taiwan. The study takes the form of qualitative research by conducting in-depth interviews of eight participants. The conclusions were divided into two categories: positive factors that aided participation and negative factors that hindered participation. The negative factors that hindered women's achievement in the field of officiating volleyball were as follows: gender stereotypes from coaches, player/fan inter-dynamics, and females' family roles and responsibilities. The most predominant positive factors that motivated personal achievement were positive family support and positive interrelationships with referee partners.